Analisis Sistem Pembayaran Klaim Polis Asuransi Beasiswa Dalam Meningkatkan Penjualan pada PT. Asuransi BAJ di Makassar - Hemy Syamsuri (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX - Sulawesi, 2013)
The aim of this study was to know the systems of the fee paid claim insurance scholarship committed by PT Asuransi BAJ Corporation Makassar. Method Used in this research was a descriptive analysis which explained about how far the corporation commits a system of the fee paid